Effect of organic farming on the restoration of soil quality, ecosystem services, and productivity in rice–wheat agro-ecosystems - Panwar, Azad S.; Ansari, Meraj A.; Ravisankar, Natesan; Babu, Subhash; Prusty, Ashisa K.; Ghasal, Prakash C.; Choudhary, Jairam; Shamim, Mohammad; Singh, Raghuveer; Raghavendra, K. J.; Dutta, Debashis; Meena, Amrit L.; et al. (Frontiers in Environmental Science, 2022)
Excess use of hazardous agrochemicals and inorganic fertilizers resulted in negative environmental outcomes and degraded soil function, biological diversity, and ecosystem services. Fifteen-year long term (2004-2018) field experiment was conducted to improve the ecosystem services with soil quality restoration and stabilization of yield through agronomic manipulation in the rice (Oryza sativa)-wheat (Triticum aestivum) system under Indo Gangetic Plains (IGP). Three crop management practices (i) organic crop management (ii) inorganic crop management (iii) integrated crop management were evaluated at four locations (i) Jabalpur (ii) Ludhiana (iii) Pantnagar (iv) Modipuram in factorial randomized block design and replicated thrice at each location. Among the spatial variation, the highest soil quality indicators like microbial biomass carbon (0.52 mg g-1), fungal (46.2 x104 CFU), bacterial (54.2 x106 CFU), actinomycetes viable cells (23.0 x106 CFU) and nutrients (available N and available P) were observed at Pantnagar than other location. Subsequently, higher system productivity (8196.7 kg ha-1) and net return were obtained in Pantnagar≥ Ludhiana and it was 44.1 to 63.4% higher over Modipuram and Jabalpur. Among the crop management, organic crop management, significantly improved (p<0.05) the soil organic carbon, available N, available P, and available K by 33.3, 16.4, 37.8, and 20.3% over inorganic crop management. Similarly, the highest bacterial, fungal, and actinomycetes viable cell counts were found under the organic plots followed by integrated plots. In terms of productivity, integrated crop management (ICM) had increased the system productivity by 4.7 to 6.7% and net returns by 22.2 and 23.5% over inorganic and organic crop management. Similarly, the highest sustainability yield index (SYI) was recorded in ICM (0.77) as compared to inorganic (0.74) and organic management (0.75). Soil quality index was estimated as 0.60, 0.53, and 0.54 in organic, inorganic, and ICM, respectively. Hence, the study indicated that the application of organic amendments under organic or integrated crop management improves the system's resiliency and sustainability. Therefore, the study concludes that towards organic approach (integrated application of organic amendments with gradual reduction in mineral fertilizers) is better suitable for keeping the rice-wheat system productive and sustainable in the long-term.